Tom Boardman : the leader as agile learner - Christierson, Viveka; Urban, Angie (London : Wits Business School, 2018)
The case describes the career of Tom Boardman from founding the Boardmans retail store in the early 1980s to becoming the chairman of Kinnevik, a Swedish investment company in 2016. The case argues that at the heart of Tom Boardman's successful career is his ability to learn throughout his long and varied career.
Originally Published InChristierson, V., & Urban, A. (2018). Tom Boardman: The leader as agile learner. WBS-2017-14. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Boardman, Tom; Boardmans; Kinnevik; Career development -- Case studies; Success in business -- Case studies